2014
DOI: 10.1021/ct4008926
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Force Decomposition for Local Stress Calculations in Biomembrane Molecular Simulations

Abstract: Local stress fields are routinely computed from molecular dynamics trajectories to understand the structure and mechanical properties of lipid bilayers. These calculations can be systematically understood with the Irving-Kirkwood-Noll theory. In identifying the stress tensor, a crucial step is the decomposition of the forces on the particles into pairwise contributions.However, such a decomposition is not unique in general, leading to an ambiguity in the definition of the stress tensor, particularly for multib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
168
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(175 citation statements)
references
References 69 publications
7
168
0
Order By: Relevance
“…7 in Ref. 20 ). Sonne and collaborators 11 showed that the pressure profile calculated using the Irving-Kirkwood approach and a cutoff radius of 2 nm is qualitatively similar to the one calculated using the Harasima path with long-range electrostatic contributions, although with an indetermination of roughly 100 to 200 bar, which makes it only a qualitative test.…”
Section: Introductionmentioning
confidence: 91%
“…7 in Ref. 20 ). Sonne and collaborators 11 showed that the pressure profile calculated using the Irving-Kirkwood approach and a cutoff radius of 2 nm is qualitatively similar to the one calculated using the Harasima path with long-range electrostatic contributions, although with an indetermination of roughly 100 to 200 bar, which makes it only a qualitative test.…”
Section: Introductionmentioning
confidence: 91%
“…In our chosen example (argon liquid film in vapor) and also for lipid bilayer [7], the inhomogeneity is in two dimensions (say, and axes) and there is no density variation along the third dimension ( axis). The computational domain is shown in figure. 2a.…”
Section: Resultsmentioning
confidence: 99%
“…However, current literature on local pressure estimation is based on 3D [3] or 1D [4][5][6] pressure estimation. The 2D pressure distribution is obtained by averaging over the 3D pressure data, and is extremely computationally expensive [7] as it involves a 3D convolution. A generalized method for 3D stress calculations which included temporal averaging weight functions was derived by Yang [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of applying Hardy stress to three-body potentials has also been discussed [56]. Only recently applications of Hardy stress to systems described by four-body potentials have been reported [63,64]. To our best knowledge, there are no examples in the literature of the use of Hardy stress in systems described by many-body potentials more involved than the original EAM potential.…”
Section: Introductionmentioning
confidence: 99%